2018
DOI: 10.1002/smll.201803585
|View full text |Cite
|
Sign up to set email alerts
|

Designable 3D Microshapes Fabricated at the Intersection of Structured Flow and Optical Fields

Abstract: of applications, including drug delivery, tissue engineering, self-assembly, and photonics. For example, the shape of hydrogel particles has been shown to affect particle-cell interactions [1][2][3] and the cross-sectional shape of microfibers changes the wicking properties of woven fabrics. [4] In addition, microobjects in nature often take on a nonequilibrium structure to exploit beneficial shapeinduced functionality, such as the biconcave geometry of the red blood cell and the triangular cross-section of Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…[16,17] In addition, spherical particles have more limited barcoding options, and it has been reported that the presence of surfactants leads to higher rates of transport of products of reactions through the continuous oil phase, reducing sensitivity of enzymatic assays. [18,19] A range of fabrication methodologies have been explored over the past decade to create particles with different shapes and functionalities using continuous [20][21][22][23][24] or stop flow lithography techniques [25][26][27][28] combined with hydrodynamic focusing, [29][30][31][32] magnetically tunable color printing, [12,33] vertical flows, [34] structured hollow fibers [35] or inertial forces. [36][37][38][39] Particles comprised of layers of hydrophobic and hydrophilic materials were shown to selectively interact and assemble around aqueous drops.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] In addition, spherical particles have more limited barcoding options, and it has been reported that the presence of surfactants leads to higher rates of transport of products of reactions through the continuous oil phase, reducing sensitivity of enzymatic assays. [18,19] A range of fabrication methodologies have been explored over the past decade to create particles with different shapes and functionalities using continuous [20][21][22][23][24] or stop flow lithography techniques [25][26][27][28] combined with hydrodynamic focusing, [29][30][31][32] magnetically tunable color printing, [12,33] vertical flows, [34] structured hollow fibers [35] or inertial forces. [36][37][38][39] Particles comprised of layers of hydrophobic and hydrophilic materials were shown to selectively interact and assemble around aqueous drops.…”
Section: Introductionmentioning
confidence: 99%
“…1b. Alternative techniques for patterning the cores axially include UV-exposure through photomasks in photopolymeric cores, resulting in non-trivially-shaped microparticles [28]. Other hybrid-functionalization techniques include coating the fiber surfaces with functional materials [10, 29] and confinement of a fiber cladding by a draw [12] to an array of optoelectronic devices fabricated by standard complementary metal-oxide-semiconductor (CMOS) manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Many current applications of flow sculpting were devised and implemented by inertial microfluidics experts, and even then, they sculpted relatively simple flow shapes that were achieved through trial-and-error design. A clear example of this difficulty is particle fabrication via flow sculpting, which remains competitive with state-of-the-art methods such as PRINT, 12 SEAL, 13 two-photon lithography, 14 and hollow fiber templating 15 due to the ability to create multi-material shaped 3D particles at high-throughput using basic microfluidic tools such as soft lithography 16 and 3D printing. 6 However, the flow sculpting approaches currently require the target 3D particle shape to comprise of the intersection of two orthogonally extruded 2D shapes: one from the shape of the sculpted flow stream (which contains a polymer precursor with a photoinitiator), and the other from an optical mask (which shapes polymerizing ultraviolet light).…”
Section: Introductionmentioning
confidence: 99%